Gender Justice in Talak: A Comparative Analysis Between Classical Fiqh and Positive Law in Indonesia - Dava Prayoga; Andi Muhammad Arya; Kurniati (PT. Nawa Edukasi Nusantara, 2026)
The phenomenon of inequality in marital relations, particularly in divorce practices, remains a significant issue in the study of family law in Indonesia. One crucial point is the concept of divorce, which shapes the distribution of power between husband and wife. This study examines the issue of gender inequality in the concept of divorce in classical Islamic jurisprudence (fiqh) and Indonesian positive law. The aim of the study is to analyze the fundamental differences between the right of divorce in both systems and to assess the resulting level of gender justice. Using a comparative literature study method, this study examines Islamic jurisprudence sources, laws and regulations, and empirical findings related to divorce practices. The results show that classical Islamic jurisprudence places the right of divorce as the husband's prerogative, creating an imbalance in power relations, while positive law provides a more equal space through divorce by divorce and divorce by lawsuit. However, the implementation of positive law still presents obstacles, such as the heavy burden of proof in divorce by lawsuit and weak guarantees of post-divorce support. The novelty of this study lies in the agreement on the reconstruction of the right of divorce, which emphasizes substantive equality between husband and wife. This proposal has the potential to strengthen women's protection and improve justice in the Indonesian family law system.